Phototransformation of tetrazoline oxime ethers: photoisomerization vs. photodegradation. Issue 7 (12th January 2016) - Fréneau, Maxime; de Sainte Claire, Pascal; Hoffmann, Norbert; Vors, Jean-Pierre; Geist, Julie; Euvrard, Michel; Richard, Claire
Abstract : Fungicides showing potent biological activity in green house may have poor activity in the field due to fast photodegradation. Abstract : Fungicides showing potent biological activity in green house may have poor activity in the field due to fast photodegradation. This is the case of tetrazoline oxime ethers1 and2, active in theZ form, on which very little is known. A comprehensive study was therefore conducted to understand the photochemical behaviour of these compounds. It could be firmly demonstrated that both photoisomerizationZ ⇄E and photodegradation occur, and that interestingly photodegradation only takes place fromE forms. Quantum yields of photoisomerization lay within the range 0.38–0.48 and those ofE photodegradation in the range 0.06–0.11. During the reaction, the non-fungicidalE forms become the major isomers due to their lower solar light absorptivity thanZ forms. The analytical study showed that photodegradation involves the cleavage of the N–O bond and allowed the identification of photoproducts arising from the rearrangement of the iminyl and alkoxyl radicals. Moreover, the proposed mechanism of alkoxyl radical oxidation into corresponding aldehyde and acid was elucidated using a computational study. This fundamental investigation fully explains the fast loss of the fungicidal activity of tetrazoline oxime ethers1 and2 in the field.